2022
DOI: 10.3389/fonc.2022.964508
|View full text |Cite
|
Sign up to set email alerts
|

A pyroptosis-related gene signature for prognostic and immunological evaluation in breast cancer

Abstract: PurposePyroptosis exerts an undesirable impact on the clinical outcome of breast cancer. Since any single gene is insufficient to be an appropriate marker for pyroptosis, our aim is to develop a pyroptosis-related gene (PRG) signature to predict the survival status and immunological landscape for breast cancer patients.MethodsThe information of breast cancer patients was retrieved from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases. Quantitative real-time polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…High levels of CXCR4 levels were expressed in more than 40% of breast tumor tissues ( 48 ) and in 75% of TNBC patients ( 49 ), and overexpression of CXCR4 in cancer cells contributes to tumor growth, invasion, metastasis, and recurrence ( 50 ). GZMB , known for stimulating anti-tumor immune responses and inhibit tumor growth ( 51 ), is correlated with favorable prognosis in breast cancer tissues ( 52 , 53 ). CCDC50 is known to mediate apoptosis via the NF-κB pathway ( 54 ) and had prognostic predictive value in lung adenocarcinoma ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of CXCR4 levels were expressed in more than 40% of breast tumor tissues ( 48 ) and in 75% of TNBC patients ( 49 ), and overexpression of CXCR4 in cancer cells contributes to tumor growth, invasion, metastasis, and recurrence ( 50 ). GZMB , known for stimulating anti-tumor immune responses and inhibit tumor growth ( 51 ), is correlated with favorable prognosis in breast cancer tissues ( 52 , 53 ). CCDC50 is known to mediate apoptosis via the NF-κB pathway ( 54 ) and had prognostic predictive value in lung adenocarcinoma ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on published research, PRGs were identified [18,19]. Using the limma package in R software, the DEGs related to pyroptosis between sepsis patients and healthy controls were analyzed, setting the thresholds at |log2FC|>1 and Padj<0.05 [17].…”
Section: Analysis Of Differentially Expressed Genes (Degs)mentioning
confidence: 99%